Mechanosensory circuits coordinate two opposing motor actions in Drosophila feeding. - Zhou, Y.; Cao, L.H.; Sui, X.W.; Guo, X.Q.; Luo, D.G. (Science advances, 2019)
Mechanoreception detects physical forces in the senses of hearing, touch, and proprioception. Here, we show that labellar mechanoreception wires two motor circuits to facilitate and terminate Drosophila feeding. Using patch-clamp recordings, we identified mechanosensory neurons (MSNs) in taste pegs of the inner labella and taste bristles of the outer labella, both of which rely on the same mechanoreceptor, NOMPC (no mechanoreceptor potential C), to transduce mechanical deflection. Connecting with distinct brain motor circuits, bristle MSNs drive labellar spread to facilitate feeding and peg MSNs elicit proboscis retraction to terminate feeding. Bitter sense modulates these two mechanosensory circuits in opposing manners, preventing labellar spread by bristle MSNs and promoting proboscis retraction by peg MSNs. Together, these labeled-line circuits enable labellar peg and bristle MSNs to use the same mechanoreceptors to direct opposing feeding actions and differentially integrate gustatory information in shaping feeding decisions.